Manfaat aloe vera sebagai terapi topikal luka bakar - Wardani, Helen Kusuma (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Aloe vera is an herbal plant that has been used extensively for centuries as a natural medicine. Aloe vera therapy activities can be used to treat skin lesions, such as burns. The gel has healing, analgesic, and anti-inflammatory activity, besides being a powerful moisturizing and protective skin agent. The speed of healing in the aloe vera group is better than the conventional group. Effects produced by aloe vera gel with reference to wound contraction, wound closure, decrease in wound surface area, tissue regeneration at the wound site. Aloe vera contains important nutrients such as vitamins A, C and E, which act as antioxidants, minerals (calcium, copper, magnesium, potassium, and zinc), enzymes, glycoproteins, amino acids, carbohydrate constituents, such as polysaccharides and salicylic acids